A PROPER ANALYSIS DIRECTED AT THE GROWTH OF THE HOTEL INDUSTRY. - gautam, Shaurya (Journal of Advanced Research in Economics and Business Management, 2023)
Training and employee development are essential in almost every business sector. Customer satisfaction is crucial to business success, and it can only be attained through good customer service training for staff. Because every position in the hospitality sector aims to increase visitor satisfaction, the importance of employee training cannot be overstated. Training and development are the responsibility of the human resources department. The process of training and development enhances the job-related skills necessary in the hospitality industry to grow the clientele. This type of dialogue could go awry and harm the hotel’s reputation if staff are not well trained in how to communicate with guests. The impact of training and development on the hotel business is discussed in this study, which also critically evaluates the performance of some of the most prestigious hotels in New Delhi while accounting for the training and development that the hotels offer to its personnel. Employee skill improvement is possible with training and development, which is crucial at this point in Covid. A SWOT analysis is used to analyse these hotels in the lack of employee training, showing their strengths, weaknesses, opportunities, and threats. For analysis corresponding to the employee in the absence of training, a correlation- and regression-based technique is applied. Finally, it was claimed that for hotels to succeed in a cutthroat economy, training should be seen as an investment rather than an expense.